Preparation method and application of carbon quantum dot composite film for movable carrier
Through the preparation of composite membranes of carbon quantum dots and polymer fiber raw materials, the material complexity and intervention problems in the existing technology are solved, and green and convenient protection of paper cultural relics is achieved, which significantly reduces the impact of ultraviolet aging. It is suitable for paper cultural relics. Anti-UV protection.
Patent Information
- Application Number
- CN202411568217.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-07
AI Technical Summary
When protecting paper cultural relics, the material preparation is complex, high cost and possible secondary degradation, and the intervention on paper cultural relics has a great impact, making it difficult to achieve green, safe and convenient non-contact protection against ultraviolet.
The carbon quantum dot composite film is prepared by ultrasonic mixing, drying, spin coating, spraying and other methods, and is attached to the mobile carrier to form a protective film with a thickness of 1-1000μm, with good ultraviolet Light shielding effect without contact intervention.
It realizes simple, green and low-cost protection of paper cultural relics, slows down cellulose photodegradation, maintains the photoluminescent properties of carbon quantum dots, significantly reduces the impact of ultraviolet aging of paper cultural relics, and is suitable for mass production.
Smart Images

Figure CN119266010A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of ancient book protection, and in particular to a method for preparing a carbon quantum dot composite film for a movable carrier and an application thereof. Background Art
[0002] As a carrier of historical information, paper artifacts have witnessed the changes of the times, and truly recorded ancient historical and cultural events, which are of great value to historical reconstruction. However, due to the influence of the external environment over time, paper artifacts are currently experiencing irreversible aging problems to varying degrees, such as yellowing, fading, and blurred text, which seriously affect the historical and collection value of paper artifacts. At present, the protection of cultural heritage is of vital importance. Among the various external factors that cause the aging of paper artifacts, the impact of light is particularly significant. High-energy ultraviolet rays can cause cellulose bonds to break, photooxidation, degradation and other reactions.
[0003] At present, in response to the UV aging of paper, a limited range of materials such as graphene, titanium dioxide and organic compounds have been studied for the UV protection of paper cultural relics. These materials are mainly contacted with paper through chemical vapor deposition, spraying, coating technology and immersion, so as to play an anti-UV protection effect on paper. However, considering the complexity of its material preparation, high cost and the possibility of secondary degradation, the complexity of its protection method, and the interference effect on paper cultural relics caused by the contact between the material and the paper cultural relics, it is very necessary to explore green and safe protection materials, convenient and convenient protection methods, and non-contact protection of paper cultural relics. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a carbon quantum dot composite film for a movable carrier and its application, which can slow down the photodegradation of cellulose in paper cultural relics, including photolysis, oxidation and acidification and other paper aging degradation. It belongs to a solid phase protection method and has no intervention or influence on paper cultural relics. The protective film maintains the photoluminescent properties of carbon quantum dots, showing a unique and practical protection mark during protection.
[0005] To achieve the above object, the present invention provides a carbon quantum dot composite film for a movable carrier, wherein the carbon quantum dot composite film for the movable carrier is composed of a composite of carbon quantum dots and a polymer fiber raw material and a dispersed solvent.
[0006] Preferably, the method for preparing a carbon quantum dot composite film for a removable carrier comprises the following steps: S1. Preparation of carbon quantum dots: Add deionized water to a carbon raw material with a mass fraction of 1%-50%, and ultrasonically mix for 10-40 minutes. Add the mixed solution to a reactor, and place the reactor in an oven at 120-200°C for reaction for 4-12 hours. Filter the reaction product, and post-treat it to obtain carbon quantum dots. S2, adding deionized water with a mass fraction of 0.1%-10% carbon quantum dots and 5%-50% polymer fiber raw materials, and stirring for 2-18 hours; S3, drying the solution obtained in step S2 into a film, with a drying temperature of 20-80° C. for 1-24 hours to obtain a carbon quantum dot composite film.
[0007] Preferably, in step S1, the carbon raw material is two or more of citric acid, aromatic amines, and amine water-soluble polymers; the post-treatment is one of dialysis for 4-36 hours, freeze drying and ethanol centrifugation, centrifugation 4-8 times, and vacuum drying at 60°C.
[0008] Preferably, the polymer fiber raw material in step S2 is cellulose ethers, including one or more of methyl, ethyl, propyl, carboxymethyl, hydroxyethyl, and hydroxypropyl.
[0009] Preferably, in step S3, the composite solution of carbon quantum dots and polymer fiber raw materials is formed into a film by spin coating, spray coating, pouring into a mold, or directly spraying or spin coating on a mobile carrier.
[0010] Preferably, the mold in step S3 includes materials such as glass, acrylic plate, metal, wood, etc. in different shapes; the mobile carrier in step S3 includes mobile carriers such as display cabinets, bookcases, picture frames, etc. of libraries, art galleries, museums, etc.
[0011] Preferably, in step S3, the carbon quantum dot composite film has a thickness of 1-1000 μm, has a certain absorption within a wavelength range of 200-400 nm, and a transmittance of more than 80% within a wavelength range of 450-700 nm.
[0012] Preferably, when the composite solution of carbon quantum dots and polymer fiber raw materials is spin-coated in step S3, the mass fraction per unit area of the solution on the mobile carrier is 0.05-5 g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃; When spraying, the mass fraction of the solution per unit area on the mobile carrier is 0.01-3g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃; When using mold processing, the mass fraction of the solution per unit area on the mobile carrier mold is 0.01-3g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃.
[0013] Preferably, the carbon quantum dot composite film is used to resist ultraviolet light aging of paper cultural relics.
[0014] Preferably, the carbon quantum dot composite film is on a mobile carrier without any contact, interference or impact on the paper.
[0015] Therefore, the present invention adopts the above-mentioned method for preparing a carbon quantum dot composite film for a movable carrier and its application, and the prepared carbon quantum dot composite paper cultural relic protection film has a layer thickness of 1-1000 μm, has a certain absorption within the wavelength of 200-400 nm, and a transmittance of more than 80% within the wavelength of 450-700 nm. The film is attached to a movable carrier and can be used for anti-ultraviolet light aging protection of paper cultural relics. Compared with the prior art, the preparation method of the present invention is simple, green and non-toxic, efficient and low-cost, convenient and convenient to protect, and can slow down the photodegradation process of cellulose in paper cultural relics. The protection of paper cultural relics by this protective film belongs to solid phase protection, and has no interference effect on paper. Therefore, the carbon quantum dot composite paper cultural relic protection film prepared by the method of the present invention is expected to be widely used in the field of paper cultural relic protection technology.
[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope (SEM) image of the surface of product A in a method for preparing a carbon quantum dot composite film for a movable carrier and its application in the present invention; Figure 2 This is a scanning electron microscope (SEM) image of a cross section of a product A in a method for preparing a carbon quantum dot composite film for a movable carrier and its application in the present invention; Figure 3 This is a method for preparing a carbon quantum dot composite film for a movable carrier and an ultraviolet absorption (UV-vis) graph of product A in its application; Figure 4 (a) Photograph and (b) luminescence photograph of a method for preparing a carbon quantum dot composite film for a movable carrier and its application product A under 365nm irradiation of the present invention; Figure 5 The present invention discloses a method for preparing a carbon quantum dot composite film for a movable carrier and a protective agent A in its application for protecting a paper sample from pH changes during ultraviolet aging; Figure 6 The present invention discloses a method for preparing a carbon quantum dot composite film for a movable carrier and a protective agent A in the application thereof, which is used for protecting a paper sample from color difference changes during ultraviolet aging. DETAILED DESCRIPTION
[0018] In order to better understand the above technical solution, the above technical solution will be described in detail below in conjunction with the accompanying drawings and specific implementation methods. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The terms used in the embodiments of the present invention are only for the purpose of describing specific embodiments, and are not intended to limit the present invention. The singular forms "a", "said" and "the" used in the embodiments of the present invention and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings, and "multiple" generally includes at least two.
[0020] It should also be noted that the term "includes", "comprising" or any other variation thereof is intended to cover non-exclusive inclusion, so that a commodity or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such commodity or device. In the absence of more restrictions, the elements defined by the sentence "comprising a ..." do not exclude the existence of other identical elements in the commodity or device including the elements.
[0021] The present application provides a carbon quantum dot composite film for a movable carrier, wherein the carbon quantum dot composite film for the movable carrier is composed of a composite of carbon quantum dots and a polymer fiber raw material and a dispersed solvent.
[0022] In order to further optimize the above technical solution, a method for preparing a carbon quantum dot composite film for a removable carrier is provided, comprising the following steps: S1. Preparation of carbon quantum dots: Add deionized water to a carbon raw material with a mass fraction of 1%-50%, and ultrasonically mix for 10-40 minutes. Add the mixed solution to a reactor, and place the reactor in an oven at 120-200°C for reaction for 4-12 hours. Filter the reaction product, and post-treat it to obtain carbon quantum dots. S2, adding deionized water with a mass fraction of 0.1%-10% carbon quantum dots and 5%-50% polymer fiber raw materials, and stirring for 2-18 hours; S3, drying the solution obtained in step S2 into a film, with a drying temperature of 20-80° C. for 1-24 hours to obtain a carbon quantum dot composite film.
[0023] To further optimize the above technical solution, the carbon raw material in step S1 is two or more of citric acid, aromatic amines, and amine water-soluble polymers; the post-treatment is dialysis for 4-36 hours, freeze drying and ethanol centrifugation, centrifugation 4-8 times, and vacuum drying at 60°C.
[0024] To further optimize the above technical solution, the polymer fiber raw material in step S2 is cellulose ethers, including one or more of methyl, ethyl, propyl, carboxymethyl, hydroxyethyl, and hydroxypropyl.
[0025] To further optimize the above technical solution, in step S3, the composite solution of carbon quantum dots and polymer fiber raw materials is formed into a film by spin coating, spraying, pouring into a mold, or directly spraying or spin coating on a mobile carrier.
[0026] To further optimize the above technical solution, the mold in step S3 includes materials such as glass, acrylic plate, metal, wood, etc. in different shapes; the mobile carrier in step S3 includes mobile carriers such as display cabinets, bookcases, picture frames, etc. of libraries, art galleries, museums, etc.
[0027] To further optimize the above technical solution, the carbon quantum dot composite film in step S3 has a thickness of 1-1000 μm, has a certain absorption within the wavelength range of 200-400 nm, and a transmittance of more than 80% within the wavelength range of 450-700 nm.
[0028] To further optimize the above technical solution, when the composite solution of carbon quantum dots and polymer fiber raw materials is spin-coated in step S3, the mass fraction per unit area of the solution on the mobile carrier is 0.05-5 g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃; When spraying, the mass fraction of the solution per unit area on the mobile carrier is 0.01-3g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃; When using mold processing, the mass fraction of the solution per unit area on the mobile carrier mold is 0.01-3g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃.
[0029] In order to further optimize the above technical solution, carbon quantum dot composite film is used to resist ultraviolet light aging of paper cultural relics.
[0030] To further optimize the above technical solution, the carbon quantum dot composite film is placed on a mobile carrier without any contact, interference or impact on the paper.
[0031] Example 1 0.8 g of citric acid, 0.2 g of o-phenylenediamine and 0.5 g of polyethyleneimine were added to 20 ml of deionized water, mixed and stirred for 20 minutes, the stirred solution was added to the reactor, placed in an oven at 160°C for reaction for 6 hours, the product was filtered, centrifuged with ethanol 4 times, and vacuum dried in an oven at 60°C to obtain carbon quantum dot solid.
[0032] Add 0.1g carbon quantum dots and 10g hydroxyethyl cellulose into 100ml deionized water and stir for 4 hours to obtain a composite solution of carbon quantum dots and hydroxyethyl cellulose. Take 3ml of the solution and spin coat it on an area of 4*4cm 2 The product was placed on a glass plate and placed in an oven at 60°C for 2 hours to obtain product A (carbon quantum dot film).
[0033] Cover product A on the surface of handmade bamboo paper and place it in a UV aging box for aging.
[0034] The original pH value of handmade bamboo paper was 5.94. After 18 days of UV aging in a UV aging box, the pH value of handmade bamboo paper without film was 4.92. The pH value of handmade bamboo paper covered with carbon quantum dot film product A was 5.26.
[0035] In the UV aging box, the color difference of the handmade bamboo paper without carbon dot film after aging for 6 days, 12 days and 18 days was 1.68, 2.71 and 3.21 respectively compared with the unaged paper. The color difference of the handmade bamboo paper covered with carbon quantum dot film product A after aging for 6 days, 12 days and 18 days was 0.81, 1.84 and 2.18.
[0036] Example 2 1 g of citric acid and 0.3 g of p-phenylenediamine were added to 20 ml of deionized water, and the mixture was stirred for 10 minutes. The stirred solution was added to a reactor, and the mixture was placed in an oven at 140° C. for reaction for 4 hours. The product was filtered, dialyzed for 24 hours, and freeze-dried to obtain a carbon quantum dot solid.
[0037] Add 0.2g carbon quantum dots and 20g carboxymethyl cellulose into 100ml deionized water and stir for 6 hours to obtain a composite solution of carbon quantum dots and carboxymethyl cellulose. Take 7.5ml of the solution and spray it on an area of 5*5cm 2 The product was placed on an acrylic plate and placed in an oven at 40°C for 6 hours to obtain product B.
[0038] Product B was placed on the surface of rice paper and placed in a UV aging box for aging. The original pH value of rice paper was 6.33. After 18 days of UV aging in the UV aging box, the pH value of the rice paper without the film was 4.85. The pH value of the rice paper covered with carbon quantum dot film product B was 5.38.
[0039] Example 3 5.0 g of citric acid and 2.5 g of polyacrylamide were added to 50 ml of deionized water, mixed and stirred for 30 minutes, the stirred solution was added to the reactor, placed in an oven at 180° C. for reaction for 8 hours, the product was filtered, centrifuged with ethanol for 5 times, and vacuum dried at 60° C. to obtain carbon quantum dot solid.
[0040] Add 2 g of carbon quantum dots and 40 g of hydroxypropyl cellulose into 200 ml of deionized water and stir for 15 hours to obtain a composite solution of carbon quantum dots and hydroxypropyl cellulose. Pour 20 ml of the solution into a 40 cm 2 The product was placed in a mold and placed in an oven at 70°C for drying for 3 hours to obtain product C.
[0041] Product C was placed on the surface of machine-made paper and placed in a UV aging box for aging. The original pH value of the machine-made paper was 5.48. After 18 days of UV aging in the UV aging box, the pH value of the machine-made paper without the film was 4.2. The pH value of the rice paper covered with the carbon quantum dot film product C was 4.83.
[0042] Example 4 2.0 g of m-phenylenediamine and 2.0 g of polyethyleneimine were added to 40 ml of deionized water, mixed and stirred for 25 minutes, the stirred solution was added to a reactor, placed in an oven at 130° C. for reaction for 4 hours, the product was dialyzed for 28 hours, and freeze-dried to obtain a carbon quantum dot solid.
[0043] Add 0.1 g of carbon quantum dots and 20 g of hydroxyethyl methyl cellulose into 50 ml of deionized water and stir for 8 hours to obtain a composite solution of carbon quantum dots and hydroxyethyl methyl cellulose. Take 50 ml of the solution and spin coat it on an area of 50 cm 2 The product was placed in a mold and placed in an oven at 20°C for drying for 3 hours to obtain product D.
[0044] Product D was placed on the surface of the leather paper and placed in a UV aging box for aging. The original pH value of the leather paper was 6.3. After 18 days of UV aging in the UV aging box, the pH value of the leather paper without the film was 5.22. The pH value of the leather paper covered with the carbon quantum dot film product D was 5.54.
[0045] Example 5 In this embodiment, carbon quantum dots and hydroxypropyl methylcellulose raw materials are mixed and stirred to prepare a carbon quantum dots and hydroxypropyl methylcellulose composite solution, and the film is covered on handmade bamboo paper with writing to carry out an aging experiment. The rest is the same as in Example 1.
[0046] Example 6 In this example, the film was prepared by spraying on a glass plate, and the glass plate with the film was covered on the Bulletin of Mathematics published by Science Press in 1956 to conduct an ultraviolet aging experiment. The rest is the same as in Example 1.
[0047] Example 7 In this embodiment, a film is prepared by a mold method, the film is covered on an acrylic display cabinet, and the acrylic plate is covered on machine-made paper with writing to carry out a UV aging experiment. The rest is the same as in Embodiment 1.
[0048] Example 8 In this embodiment, the amount of the composite solution sprayed on the acrylic plate is changed to configure carbon dot films of different thicknesses on the acrylic plate. The rest is the same as in Embodiment 2.
[0049] Figure 1 This is a SEM image of the surface of the carbon quantum dot film of product A of the present invention. It can be seen that the carbon quantum dot protective film prepared by the present invention has a nano-scale smooth surface.
[0050] Figure 2 This is a SEM image of the cross section of the carbon quantum dot film of product A of the present invention. It can be seen that the carbon quantum dot protective film prepared by the present invention has a thickness of about 17 um and is dense in the height direction.
[0051] Figure 3 This is the ultraviolet absorption (UV-VIS) graph of the carbon quantum dot film of product A of the present invention. It can be seen from the graph that the carbon quantum dot protective film prepared by the present invention has good absorption at 200-400nm. By evaluating the ultraviolet light shielding rate of product A at 225nm and 350nm, it is found that product A has a certain ultraviolet shielding effect.
[0052] Figure 4 (a) Photograph and (b) luminescence photograph under 365nm irradiation of a method for preparing a carbon quantum dot composite film for a removable carrier and a paper cultural relic anti-ultraviolet degradation protection product A of the present invention, from Figure 4 (a) It can be seen that product A is transparent and does not affect the light transmittance of the glass plate. Figure 4 (b) It can be seen that due to the photoluminescent properties of carbon quantum dots, the obtained carbon quantum dot film product A also has photoluminescent properties, emitting uniform blue light under 365nm ultraviolet excitation, which can easily identify the carbon quantum dots distributed in the paper, which is also a unique and practical mark in the protective film.
[0053] Figure 5 The carbon quantum dot film product A of the present invention is used for paper sample protection. The pH value of the paper changes in a 40W UV aging box. It can be seen that under 18 consecutive days of UV aging conditions, the pH value of the handmade bamboo paper covered with protective film A dropped from 5.94 to 5.26, while the pH value of the paper not covered with the protective film was 4.92. The pH value of the handmade bamboo paper covered with protective film A is significantly higher than the pH value of the paper without the protective film, indicating that the handmade bamboo paper treated with protective film A can slow down the degradation of paper by ultraviolet rays, thereby protecting the paper.
[0054] Figure 6The carbon quantum dot film of this product A is used to protect the color difference of paper in a 40W UV aging box. It can be seen that after 6 days, 12 days and 18 days of UV aging, the color difference of unprotected handmade bamboo paper changes by 1.68, 2.71 and 3.21 respectively, while the color difference of handmade bamboo paper covered with protective film is 0.81, 1.84 and 2.18 respectively. The color difference value of handmade bamboo paper covered with protective film A is significantly lower than that of unprotected base paper, indicating that handmade bamboo paper covered with protective film A has a protective effect against light UV aging.
[0055] Therefore, the carbon quantum dot composite film for movable carriers prepared by the method of the present invention has a nano-scale smooth surface, is highly dense in the direction, and has a thickness of 1-1000 μm. The carbon quantum dot film can be attached to the mobile carriers such as picture frames, display cabinets and bookcases of various collections by spin coating, spray coating, mold method or direct film formation on the mobile carrier. It has a good ultraviolet shielding effect in ultraviolet absorption and is a good anti-ultraviolet protective film. Compared with the prior art, the synthesis method of the present invention is simple, green and environmentally friendly, low in cost, and the protection method is convenient and fast, without any contact intervention and influence on paper cultural relics. Due to the maintenance of the photoluminescent properties of carbon quantum dots, the protection of paper cultural relics has a unique and practical mark, and can slow down the photodegradation process of paper cellulose caused by light, and is suitable for mass production of low-cost anti-ultraviolet protection for paper. It can be seen that the carbon quantum dot composite paper cultural relic protection film that can be used for mobile carriers prepared by the method of the present invention is expected to have good application prospects in the field of paper cultural relic protection technology.
[0056] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. A carbon quantum dot composite film for a removable carrier, characterized in that: The carbon quantum dot composite film of the movable carrier is composed of a composite of carbon quantum dots and a polymer fiber raw material and a dispersed solvent.
2. The method for preparing a carbon quantum dot composite film for a movable carrier according to claim 1, characterized in that: The following steps are involved: S1. Preparation of carbon quantum dots: Add deionized water to a carbon raw material with a mass fraction of 1%-50%, and ultrasonically mix for 10-40 minutes. Add the mixed solution to a reactor, and place the reactor in an oven at 120-200°C for reaction for 4-12 hours. Filter the reaction product, and post-treat it to obtain carbon quantum dots. S2, adding deionized water with a mass fraction of 0.1%-10% carbon quantum dots and 5%-50% polymer fiber raw materials, and stirring for 2-18 hours; S3, drying the solution obtained in step S2 into a film, with a drying temperature of 20-80° C. for 1-24 hours to obtain a carbon quantum dot composite film.
3. The method for preparing a carbon quantum dot composite film for a movable carrier according to claim 2, characterized in that: In step S1, the carbon raw materials are two or more of citric acid, aromatic amines, and amine water-soluble polymers; the post-treatment is one of dialysis for 4-36 hours, freeze drying and ethanol centrifugation, centrifugation for 4-8 times, and vacuum drying at 60°C.
4. A method for preparing a carbon quantum dot composite film for a removable carrier according to claim 3, characterized in that: In step S2, the polymer fiber raw material is cellulose ethers, including one or more of methyl, ethyl, propyl, carboxymethyl, hydroxyethyl, and hydroxypropyl.
5. The method for preparing a carbon quantum dot composite film for a movable carrier according to claim 4, characterized in that: In step S3, the composite solution of carbon quantum dots and polymer fiber raw materials is formed into a film by spin coating, spray coating, pouring into a mold, or directly spraying or spin coating on a mobile carrier.
6. The method for preparing a carbon quantum dot composite film for a movable carrier according to claim 5, characterized in that: The mold in step S3 includes materials such as glass, acrylic plate, metal, wood, etc. in different shapes; the mobile carrier in step S3 includes mobile carriers such as display cabinets, bookcases, picture frames, etc. of libraries, art galleries, museums, etc.
7. The method for preparing a carbon quantum dot composite film for a movable carrier according to claim 6, characterized in that: The carbon quantum dot composite film in step S3 has a thickness of 1-1000 μm, has a certain absorption within the wavelength range of 200-400 nm, and a transmittance of more than 80% within the wavelength range of 450-700 nm.
8. The method for preparing a carbon quantum dot composite film for a movable carrier according to claim 7, characterized in that: In step S3, when the composite solution of carbon quantum dots and polymer fiber raw materials is subjected to spin coating, the mass fraction per unit area of the solution on the mobile carrier is 0.05-5 g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃; When spraying, the mass fraction of the solution per unit area on the mobile carrier is 0.01-3g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃; When using mold processing, the mass fraction of the solution per unit area on the mobile carrier mold is 0.01-3g / cm 2 , drying time is 1-24 hours, temperature is 20-80℃.
9. The use of a carbon quantum dot composite film for a movable carrier according to claim 8, characterized in that: The carbon quantum dot composite film is used for resisting ultraviolet light aging of paper cultural relics.
10. The use of a carbon quantum dot composite film for a movable carrier according to claim 9, characterized in that: The carbon quantum dot composite film is on a mobile carrier and has no contact, interference or impact on the paper.
Citation Information
Patent Citations
Multifunctional nano compound treating fluid for protecting paper cultural relics and preparation method thereof
CN103276627A
Preparation method of carbon quantum dot fluorescent paper
CN114108374A
Anti-aging fluorescent carbon quantum dot antibacterial functional film
CN117487226A
Preparation method and application of carbon dot flexible high-visible-light-transmittance anti-ultraviolet film
CN118702940A
